The Effect of Net Interest Margin Ratio, Capital Adequacy Ratio and Return on Assets at Commercial Banks on Gross Domestic Product Before and after the Covid-19 Pandemic in Indonesia - Ahmad Zaki (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
Covid-19 has had an impact on the Indonesian banking industry, slowing down the rate of economic growth, one of which is caused by slowing credit growth in the community, resulting in decreased profitability in banks. The goal of this study is to examine bank financial performance before and after the Covid-19 outbreak, as well as to provide alternative techniques for improving Indonesian bank financial performance. The data used in this research is secondary data obtained from annual reports on audited banking from 2018 to 2021, which can be accessed on the IDX website. This study employs multiple regression data analysis to assess performance using three financial ratios:Net Interest Margin, Capital Adequacy Ratioand Return On Assetsto GDP. The findings of this study show that theNet Interest Margin, Capital Adequacy Ratio and Return On Assetsvariables have a significant positive effect on GDP in the phenomena before and after the Covid-19 pandemic